2022
DOI: 10.3390/ijms23095055
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated Hyaluronan Binds to Heparanase and Blocks Its Enzymatic and Cellular Actions in Carcinoma Cells

Abstract: We examined whether sulfated hyaluronan exerts inhibitory effects on enzymatic and biological actions of heparanase, a sole endo-beta-glucuronidase implicated in cancer malignancy and inflammation. Degradation of heparan sulfate by human and mouse heparanase was inhibited by sulfated hyaluronan. In particular, high-sulfated hyaluronan modified with approximately 2.5 sulfate groups per disaccharide unit effectively inhibited the enzymatic activity at a lower concentration than heparin. Human and mouse heparanas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
0
0
Order By: Relevance
“…A crystallographic study of Hpse demonstrated the location of these anionic amino acid residues relatively inside of the enzyme molecule [ 53 ]. It is speculated that the negative charge itself can be repulsive for the binding of Hpse to HS, which is also supported by our previous physicochemical study [ 54 ]. Heparastatin (SF4), a compound optimized for inhibition of Hpse enzymatic activity, is a derivative of a bacterial product siastatin B that can inhibit the enzymatic activity of Hpse.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…A crystallographic study of Hpse demonstrated the location of these anionic amino acid residues relatively inside of the enzyme molecule [ 53 ]. It is speculated that the negative charge itself can be repulsive for the binding of Hpse to HS, which is also supported by our previous physicochemical study [ 54 ]. Heparastatin (SF4), a compound optimized for inhibition of Hpse enzymatic activity, is a derivative of a bacterial product siastatin B that can inhibit the enzymatic activity of Hpse.…”
Section: Discussionsupporting
confidence: 79%
“…The binding of Hpse to immobilized heparin or GAG derived from MST cells was examined based on an ELISA-like method as described previously [ 49 , 54 ]. Briefly, streptavidin was immobilized onto the ELISA plate (Greiner, Frickenhausen, Germany, 655061).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation